Engineering the nanostructure of a polymer-nanocomposite film containing Ti-based core-shell particles to enhance dielectric response. - Mahadevegowda, A; Young, N; Grant, P (Royal Society of Chemistry, 2015)
Nylon-6 based polymer-nanocomposite (PNC) dielectrics containing nano-regions of Ti-only and Ag + Ti have been manufactured by layer-by-layer deposition. By varying the thickness and deposition rate of individual layers, the PNC structure was manipulated at the nano-scale and then studied using various types of transmission electron microscopy (TEM). Enhanced PNC dielectric properties, with a dielectric constant k as high as ∼73, were shown to relate critically to in situ reactions and the detailed nano-arrangement of the resulting Ti (core)-TiOx (shell) and Ag nanoparticles.